Исследование параметров водно-спиртовых смесей полученных в условиях знакопеременных импульсов давления - Шурчкова, Юлия Александровна; Дубовкина, Ирина Александровна (НТУ "ХПИ", 2015)
Представлены результаты исследований параметров водно-спиртовых смесей полученных в условиях знакопеременных импульсов давления. Исследованы различные температурные режимы и время обработки водно-спиртовых смесей в интервале концентраций 10-90% об. В результате проведенных исследований установлено, что водно-спиртовые смеси, полученные в условиях знакопеременных импульсов давления, содержат меньшее количество вредных примесей, растворенного кислорода, обладают улучшенными органолептическими свойствами, что свидетельствует об улучшенных физико-химических свойствах.

The purpose of this work is study the impact of non-reagent method, namely alternating impulses of pressure on the parameters of water-ethanol mixtures in a wide range of concentrations. Object of research is hydrodynamic processes in the processing of water-ethanol mixtures using mechanisms of discrete-pulsed input of energy. Modular system for the study selected of water-ethanol mixtures in a broad range of concentrations. In this paper used the method of electrochemical potentiometric measurements, chromatographic studies to studies micro admixtures in water-ethanol mixtures. The results of studies of the parameters of water-ethanol mixtures obtained under alternating pressure pulses. We explore different process conditions and the processing of water-ethanol mixtures in a concentration range of 10-90%. That was the set, something happening reduction quantity of oxygen in the water-ethanol mixtures and slowing oxidation reactions.
Research parameters of the water-ethanol mixture obtained under conditions of alternating impulses of pressure
Keywords: процесс смешивания; вредные примеси; дискретно-импульсное введение энергии; сверхчастотная обработка; СВЧ; mixing process; harmful impurities